High-temperature-resistant functional current collector, preparation method thereof, pole piece and battery

CN123017974APending Publication Date: 2026-10-30YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611018206.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明的目的是克服现有集流体高温易分层、热量积聚明显、电化学性能衰减快的缺陷,提供一种耐高温功能集流体及其制备方法、极片和电池

Benefits of technology

本发明的吸波改性金属网格结构的网格空隙几何约束,能够使吸波材料纳米氮化硅、石墨烯定向排布,增强局域电场集中效应;本发明将增强抗高温层改为网状结构而非连续层,可兼顾超声波吸收与导电连续性;同时利用金属网格的电容效应增强局域电场,可提升吸波材料对电磁波的捕获效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017974A_ABST
    Figure CN123017974A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high-temperature-resistant functional current collector and preparation method thereof, pole piece and battery, comprising: polymer substrate layer and metal layer, the polymer substrate layer and metal layer between being equipped with wave-absorbing layer, the wave-absorbing layer is the wave-absorbing modified metal grid structure formed in the side of metal layer towards polymer substrate layer.The application realizes the directional arrangement of wave-absorbing material by the geometric constraint of grid structure, enhances local electric field effect, and the net structure guarantees ultrasonic wave absorption performance, and maintains the continuity of electric conduction, and the capacitance effect of metal grid significantly improves electromagnetic wave capture efficiency, and the method greatly improves the high-temperature resistance and electrochemical performance of battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to a high-temperature resistant functional current collector and its preparation method, as well as an electrode and a battery. Background Technology

[0002] Lithium-ion batteries are now widely used in new energy vehicles, energy storage equipment, digital products and other fields. As the use scenarios of high power and high rate of equipment continue to increase, the proportion of batteries in frequent fast charging and discharging and high temperature operation conditions continues to increase, which puts forward stringent requirements on the heat resistance stability, interfacial bonding strength and electrochemical compatibility of the internal current collector.

[0003] Traditional composite current collectors generally adopt a structure in which a polymer substrate is directly bonded to a metal layer. The two types of materials have a large difference in thermal expansion coefficients. During long-term high-temperature service and repeated charge-discharge heat generation, delamination and peeling problems are prone to occur between the layers. At the same time, conventional current collectors have weak electromagnetic wave and ultrasonic energy absorption capabilities, and heat is easily accumulated in the local charging and discharging area, forming hot spots. This not only easily induces microscopic damage at the interface, but also accelerates side reactions in the electrolyte, causing rapid decay of battery cycle capacity and making it difficult to guarantee high-temperature safety.

[0004] Furthermore, during the ultrasonic welding process of the battery cell tabs, insufficient heat resistance of the current collector makes it prone to cracking defects under the heat of welding, further reducing the conductivity reliability of the electrode and the battery life. Existing technologies mostly optimize the substrate material and the thickness of the metal coating, failing to simultaneously address heat resistance, energy absorption, and interfacial bonding performance at the level of interlayer functional structure, making it difficult to meet the high-load, high-temperature battery usage requirements. Therefore, developing a functional current collector with high temperature resistance, good structural stability, and excellent electrochemical performance has practical application value. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing current collectors, such as easy stratification at high temperatures, significant heat accumulation, and rapid degradation of electrochemical performance, and to provide a high-temperature resistant functional current collector, its preparation method, electrode, and battery.

[0006] To achieve the above objectives, the technical solution provided by the present invention is as follows: The first aspect of this application provides a high-temperature resistant functional current collector, comprising: a polymer substrate layer and a metal layer, wherein an absorbing layer is provided between the polymer substrate layer and the metal layer, the absorbing layer being an absorbing modified metal mesh structure formed on the side of the metal layer facing the polymer substrate layer, and the absorbing modified metal mesh structure being an integrated composite functional structure composed of a metal mesh and absorbing material filling the mesh gaps.

[0007] To optimize the above technical solution, the specific limitations also include: It also includes a thermal buffer transition layer, which is located between the microwave absorbing layer and the polymer substrate layer.

[0008] The second aspect of this application provides a method for preparing a high-temperature resistant functional current collector, comprising the following steps: S1: Metal foil pretreatment; S2: Photosensitive polyimide is coated on one side of a metal foil, and a grid-like mask gap is formed after ultraviolet exposure and development; S3: Apply a microwave absorbing enhancement layer slurry to one side of the metal foil with a grid-like mask gap, so that the slurry fills the mask gap and forms a composite metal foil with a microwave absorbing modified metal grid structure. S4: High-temperature curing of composite metal foil with microwave-absorbing modified metal mesh structure; S5: Hot-press the side of the composite metal foil with the microwave-absorbing modified metal mesh structure to the polymer substrate.

[0009] To optimize the above technical solution, the specific measures also include: The metal foil pretreatment in step S1 is plasma cleaning, and the cleaning gas is a mixture of Ar and H2.

[0010] Furthermore, in step S2, a 50-100 μm mesh-free area is reserved at the edge of the metal foil.

[0011] The microwave absorbing reinforcement layer slurry comprises 10-20% by mass of nano-silicon nitride, 3-8% of graphene, and 5-12% of organic binder.

[0012] Furthermore, between steps S4 and S5, the following steps are provided: applying a heat buffer material to one side of the composite metal foil with a wave-absorbing modified metal mesh structure and curing it.

[0013] The heat buffer material comprises the following components by mass fraction: 40-50% modified silicone resin, 20-30% boron nitride nanosheets, 10-15% silica aerogel, 0.3-0.5% platinum catalyst, and 2-4.5% epoxy silane coupling agent; The curing process is a stepped curing process, including the following stages: Curing at 75-80℃ for 40-45 seconds in air atmosphere to induce gelation; Curing at 120-130℃ for 80-90 seconds under N2 atmosphere to form crosslinks; Curing is carried out under vacuum at 60-65℃ for 4-5 minutes to allow the product to mature.

[0014] A third aspect of this application provides an electrode comprising the aforementioned high-temperature resistant functional current collector.

[0015] A fourth aspect of this application provides a battery comprising the aforementioned electrode.

[0016] Compared with the prior art, the beneficial effects of the present invention are: The geometric constraint of the mesh gaps in the microwave-absorbing modified metal mesh structure of this invention enables the directional arrangement of microwave-absorbing materials such as nano-silicon nitride and graphene, thereby enhancing the local electric field concentration effect. This invention changes the high-temperature-resistant layer to a mesh structure rather than a continuous layer, which can balance ultrasonic absorption and electrical conductivity continuity. At the same time, the capacitance effect of the metal mesh is used to enhance the local electric field, thereby improving the microwave-absorbing material's electromagnetic wave capture efficiency.

[0017] The method of the present invention avoids the use of photoresist to prepare mesh-like mask gaps, and instead uses photosensitive polyimide to prepare mesh-like mask gaps. On the one hand, photoresist stripping may cause damage and easily lead to defects at the edge of the absorbing layer. On the other hand, using photosensitive polyimide to replace traditional photoresist to prepare mesh-like mask gaps can be retained as an adhesive layer after exposure without the need for stripping, thereby improving the mechanical properties of the current collector.

[0018] Furthermore, the present invention adds a thermal buffer transition layer between the metal layer and the polymer substrate to avoid the risk of delamination between the polymer substrate and the metal layer under long-term high-temperature environment due to the difference in thermal expansion coefficient. Attached Figure Description

[0019] Figure 1 : A schematic diagram of the high-temperature resistant functional current collector of the present invention.

[0020] In the diagram: 1-polymer substrate layer, 2-metal layer, 3-wave absorbing layer, 4-thermal buffer transition layer. Detailed Implementation

[0021] The present invention will be further described in detail below through specific embodiments, but it should not be construed as limiting the scope of the subject matter of the present invention to the following embodiments. All technologies implemented based on the above content of the present invention fall within the scope of the present invention.

[0022] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the reagents, methods and equipment used are conventional reagents, methods and equipment in this technical field.

[0023] This invention provides a high-temperature resistant functional current collector, comprising: a polymer substrate layer and a metal layer, wherein an absorbing layer is provided between the polymer substrate layer and the metal layer, the absorbing layer being an absorbing modified metal mesh structure formed on the side of the metal layer facing the polymer substrate layer, and the absorbing modified metal mesh structure being an integrated composite functional structure composed of a metal mesh and absorbing material filling the mesh gaps.

[0024] This invention comprises a polymer substrate layer, a metal layer, and an intermediate microwave-absorbing modified metal mesh structure. The regular arrangement of the microwave-absorbing material by the mesh geometry can enhance the local electric field effect, taking into account both ultrasonic absorption capability and conductivity continuity. The electromagnetic wave capture efficiency is improved through the mesh capacitance effect, and the overall high-temperature resistance and electrochemical performance of the current collector are improved.

[0025] In some embodiments, a thermal buffer transition layer is provided on the outside of the polymer substrate, and the thermal buffer transition layer is located between the microwave absorbing layer and the polymer substrate layer.

[0026] The added thermal buffer transition layer can buffer the stress caused by the difference in thermal expansion coefficients of the two substrates, effectively avoid the problem of interlayer delamination under long-term high-temperature conditions, and improve the overall stability of the composite structure.

[0027] In some embodiments, the metal layer is a copper or aluminum metal layer with a thickness of 0.5~1.0 μm; The polymer substrate layer can be made of various materials such as polyethylene terephthalate (PET), polypropylene (PP), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene, polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyphenylene oxide (PPO), polystyrene (PS), and polyimide (PI); the thickness of the polymer substrate layer is 3~10μm; This invention also provides a method for preparing a high-temperature resistant functional current collector, comprising the following steps: S1: Metal foil pretreatment; S2: Photosensitive polyimide is coated on one side of a metal foil, and a grid-like mask gap is formed after ultraviolet exposure and development; S3: Apply a microwave absorbing enhancement layer slurry to one side of the metal foil with a grid-like mask gap, so that the slurry fills the mask gap and forms a composite metal foil with a microwave absorbing modified metal grid structure. S4: High-temperature curing of composite metal foil with microwave-absorbing modified metal mesh structure; S5: Hot-press the side of the composite metal foil with the microwave-absorbing modified metal mesh structure to the polymer substrate.

[0028] The method of the present invention avoids the use of photoresist to prepare mesh-like mask gaps, and instead uses photosensitive polyimide to prepare mesh-like mask gaps. On the one hand, photoresist stripping may cause damage and easily lead to defects at the edge of the absorbing layer. On the other hand, using photosensitive polyimide to replace traditional photoresist to prepare mesh-like mask gaps can be retained as an adhesive layer after exposure without the need for stripping, thereby improving the mechanical properties of the current collector.

[0029] The metal foil pretreatment in step S1 is plasma cleaning, using a mixture of Ar and H2 gas, with Ar accounting for more than 90%. This plasma cleaning removes oxides from the metal surface and improves adhesion.

[0030] In some embodiments, the grid line width is 0.5~0.8μm, the mesh size is 2~4μm, and the layer thickness is 0.3~0.5μm; in some embodiments, step S2 reserves a 50~100μm mesh-free area at the edge of the metal foil. The reserved mesh-free area at the edge of the metal foil eliminates the edge electric field effect caused by the grid structure, avoids local performance abnormalities at the edge, and improves the overall uniformity of the current collector.

[0031] In some embodiments, the microwave absorbing enhancement layer slurry comprises 10-20% by mass of nano-silicon nitride, 3-8% by mass of graphene, and 5-12% by mass of organic binder, with NMP as the solvent; specifically, the viscosity of NMP is preferably 2000-5000 cP.

[0032] In some embodiments, the coating in step S3 is performed by slot extrusion coating. After coating the microwave absorption enhancement layer slurry, the solvent is removed by vacuum drying at 120~150°C. The thickness of the layer after solvent removal is approximately 80~100 nm.

[0033] In some embodiments, the high-temperature curing in step S4 is a heat treatment at 230~280°C in an inert atmosphere. During this process, graphene forms Cu-OC chemical bonds with the metal interface, which can optimize the interface, reduce the interface resistance, enhance thermal conductivity, promote the conversion of electromagnetic energy to thermal energy, and enhance adhesion.

[0034] Between steps S4 and S5, the following steps are also provided: applying a heat buffer material to one side of the composite metal foil with a wave-absorbing modified metal mesh structure and curing it.

[0035] The heat buffer material comprises the following components by mass fraction: 40-50% modified silicone resin, 20-30% boron nitride nanosheets, 10-15% silica aerogel, 0.3-0.5% platinum catalyst, and 2-4.5% epoxy silane coupling agent, with ethyl acetate as the solvent. The modified silicone resin serves as the elastic matrix, while the boron nitride nanosheets and silica aerogel optimize the thermal effect. The platinum catalyst promotes curing, and the epoxy silane coupling agent strengthens the interfacial bonding. The hierarchical thermal insulation network formed by the boron nitride nanosheets and silica aerogel significantly delays thermal shock during hot pressing and use.

[0036] The curing process is a stepped curing process, including the following stages: Curing at 75~80℃ for 40~45 seconds in air atmosphere to gel the gel; this stage fixes the shape and prevents sagging. Curing at 120-130℃ for 80-90 seconds under N2 atmosphere, cross-linking is formed, and an elastic network is formed during this stage; Curing at 60-65℃ under vacuum for 4-5 minutes allows for maturation and eliminates internal stress during this stage. After three stages of solidification, the conversion rate can reach over 95%.

[0037] The stepped curing process of this invention completes gel formation, cross-linking formation and stress release step by step through graded curing. The internal structure of the material is dense and uniform, with excellent heat insulation and buffering effect, high interfacial bonding strength, and significantly improved thermal shock resistance.

[0038] The initial wet film coating thickness of the heat buffer material is 500~700nm, and the final cured thickness is 100~200nm.

[0039] In step S5, the side of the composite metal foil with the microwave-absorbing modified metal mesh structure is hot-pressed with the polymer substrate. The hot-pressing temperature is controlled according to the selected polymer substrate to prevent deformation of the polymer substrate.

[0040] The present invention also provides an electrode comprising the above-mentioned high-temperature resistant functional current collector.

[0041] The present invention also provides a battery comprising the above-described electrode.

[0042] The technical solution of the present invention will be further described in detail below with reference to specific embodiments: Example 1 1. Material Preparation Metal foil: 1μm electrolytic copper foil; Polymer substrate: 7μm polyethylene terephthalate (PET) film; Microwave absorbing paste: 15% nano-silicon nitride with a particle size of 50nm, 5% graphene, 8% polyamide-imide binder, and NMP with a viscosity of 3500cP as the solvent; Thermal buffer material: 45% methylphenyl silicone resin, 25% boron nitride nanosheets with a thickness of <100nm, 12% silica aerogel with a pore size of about 20nm, 0.4% platinum catalyst and 3% epoxy silane coupling agent, with ethyl acetate as the solvent; 2. Preparation of composite metal foil: Metal pretreatment: Copper foil was cleaned using Ar / H2=95 / 5 plasma, with the following conditions: power 300W, gas pressure 50Pa, and processing time 120s. Mesh mask preparation: Coated with an 8μm thick layer of photosensitive polyimide, exposed to 365nm UV light at an energy of 200mJ / cm². 2This forms a grid pattern with a line width of 0.6μm and a mesh size of 3μm, with an 80μm non-mesh area reserved at the edge; Wave-absorbing layer molding: The microwave absorbing paste is applied to the slits with a slit gap of 50 μm and a speed of 2 m / min; after vacuum drying at 150℃, a 90 nm thick composite layer is formed; during heat treatment in a nitrogen atmosphere at 250℃, Cu-OC bonds are formed at the interface between graphene and copper. Heat buffer layer construction: A heat-absorbing material is coated to a wet film thickness of 600 nm, followed by three-step curing: 78℃ / 45s air, 125℃ / 85s N2, 63℃ / 4.5min vacuum; A thermal buffer layer with a thickness of approximately 160 nm was ultimately obtained.

[0043] Hot pressing composite: After hot pressing at 0.8 MPa and 180℃ for 30 seconds, the interfacial peel strength reached 3.2 N / cm.

[0044] 3. Performance Characterization: The composite metal foil prepared in step 2 is used as the negative electrode current collector. A silicon-carbon negative electrode slurry (80% nano silicon-carbon, 10% conductive carbon black, and 10% PVDF binder) is directly coated on it and dried at 120°C to form the negative electrode. The positive electrode uses aluminum foil current collector coated with lithium iron phosphate slurry (LFP:C=90:5:5); Electrolytes and Packaging: A gel electrolyte (PVDF-HFP / LiTFSI / EC-PC) is used, coated between the positive and negative electrodes.

[0045] 4. Performance Characterization: Cycle life 1C / 1C, 25℃, 500 cycles, capacity retention 85%, Cu-OC bonds formed at high temperature enhance interface stability, methylphenyl silicone resin effectively alleviates electrode pulverization caused by thermal stress. The rate performance is 0.2C to 5C stepped charging. The 5C capacity is 91% of the 0.2C capacity. The microwave-absorbing modified metal mesh structure of this invention enhances the local electric field concentration effect, takes into account both ultrasonic absorption and conductivity continuity, and improves the charge transfer efficiency of the local electric field. At the same time, the nano silicon nitride microwave-absorbing layer and the gradient curing thermal buffer layer work together to achieve rapid heat dissipation. High-temperature safety: No thermal runaway was observed after 2.5 hours of storage at 200℃. The boron nitride nanosheets and silica aerogel in the heat buffer layer effectively blocked heat diffusion, while the silicone resin matrix maintained structural stability.

[0046] Example 2 This embodiment differs from Embodiment 1 in that the ratio of the microwave absorbing slurry is adjusted: 10% nano-silicon nitride, 8% graphene, and 12% organic binder, while the remaining raw materials and preparation process parameters remain the same.

[0047] After the battery was assembled and tested, the 5C rate capacity reached 90.2% of the 0.2C capacity; the capacity retention rate was 82.7% after 500 cycles; and the structure remained intact and without abnormalities after 2.5 hours of storage at 200℃. The high graphene content further optimized the conductivity and transmission efficiency, and the reduced silicon nitride content still maintained the basic high-temperature protection capability.

[0048] Example 3 This embodiment differs from Embodiment 1 in that the grid line width is set to 0.5μm, the mesh size is 2μm, and a 50μm non-mesh area is reserved at the edge, while the other conditions remain unchanged.

[0049] Test results: interlayer peel strength was 3.05 N / cm; heat dissipation rate was improved; local maximum temperature during charging and discharging decreased slightly compared to Example 1; mesh refinement enhanced the local electric field confinement effect; electromagnetic capture efficiency was slightly improved; and cycle stability remained basically the same.

[0050] Comparative Example 1 The scheme of this comparative example is basically the same as that of Example 1, except that the heat treatment in a nitrogen atmosphere at 250°C is replaced with a heat treatment in a nitrogen atmosphere at 150°C during the formation of the absorbing layer.

[0051] Tests showed that the 150℃ heat treatment resulted in insufficient formation of Cu-OC bonds at the graphene-copper interface, causing the capacity retention rate to drop to 67% during cycling tests; charge transfer was hindered, and the capacity at 5C rate was only 72% of that at 0.2C.

[0052] Comparative Example 2 The scheme of this comparative example is basically the same as that of Example 1, except that the wave-absorbing modified metal mesh structure is not set, and copper foil is directly coated with heat buffer material to construct the heat buffer layer.

[0053] Testing revealed that some products in the comparative sample experienced thermal-electric coupling imbalance, resulting in a 30-37% decrease in ultrasonic absorption efficiency. During charging and discharging, the temperature of local hot spots increased by 12-15°C, leading to electrolyte decomposition and bubbles during high-temperature storage testing.

[0054] Comparative Example 3 The scheme in this comparative example is basically the same as that in Example 1, except that a thermal buffer layer is not provided.

[0055] Tests showed that when the comparative sample was stored at 200°C for about 1.5 hours, some products experienced thermal runaway, product delamination, and reduced heat resistance.

[0056] Comparative Example 4 The scheme of this comparative example is basically the same as that of Example 1, except that the photosensitive polyimide is replaced with photoresist, and the composite metal foil with the microwave-absorbing modified metal mesh structure is cured at high temperature after peeling.

[0057] The photosensitive polyimide layer retained in Example 1 can serve as a permanent adhesive layer, while Comparative Example 4 reduced the peel strength test data by 18-22% compared to Example 1; and the photoresist peeling process causes edge tearing, resulting in the loss of the absorbing layer.

[0058] Comparative Example 5 Compared to Example 1, the absorbing layer adopts a solid continuous film structure: the grid pattern forming process is omitted during preparation, and the absorbing paste is coated on the entire surface of the metal foil to form a complete continuous absorbing film without any perforations. The remaining components and preparation process are completely the same.

[0059] Test results: The continuity of the conductive path is blocked, and the internal resistance increases significantly; the 5C rate capacity is only 76% of that of 0.2C; the uniformity of ultrasonic energy absorption deteriorates, and thermal damage is prone to occur at the weld joint, making it impossible to meet the dual requirements of wave absorption and heat dissipation as well as conductive transmission.

[0060] Comparative Example 6 Compared to Example 1, the heat buffer layer uses only a single curing temperature of 125°C and a single curing time of 125 seconds, instead of a stepped, segmented curing process.

[0061] Test results: The material has high residual internal stress, and micro-cracks appear at the interface after hot pressing; slight debonding occurs between layers under high temperature conditions, and the capacity retention rate drops to 71.3% after 500 cycles, resulting in a significant decrease in thermal insulation and buffering performance.

[0062] Comparative Example 7 Compared to Example 1, the microwave absorbing paste contains no graphene component, retaining only nano-silicon nitride and binder, while the other parameters remain unchanged.

[0063] Test results: It is difficult to form chemical bonds between layers, resulting in increased interfacial contact resistance; charge transfer is slow, rate performance declines significantly, heat dissipation and thermal conductivity are insufficient at high temperatures, and the battery's high-temperature tolerance is significantly worse.

[0064] The specific test results for each case are shown in Table 1.

[0065] Table 1

[0066] Analysis of experimental conclusions: Examples 1, 2, and 3 focus on adjusting the proportion of microwave absorbing slurry components and the mesh morphology parameters. Changes in the proportion and mesh size within a reasonable range will not significantly impair the battery cycle life and high-temperature stability, but will only slightly affect the charge transport and interface bonding effect. The parameters within the appropriate range can ensure the basic performance of the current collector.

[0067] Comparing the differences in heat treatment conditions, in Comparative Example 1, lowering the curing temperature prevented the effective formation of interfacial chemical bonds, weakening the interlayer bonding and directly impacting the battery's rate discharge and cycle performance. Comparative Example 5, by abandoning the perforated mesh structure and replacing it with a continuous film layer, disrupted the conductive pathway arrangement, making it impossible to simultaneously meet the requirements of electromagnetic wave absorption and conductive transmission, resulting in a simultaneous decline in overall electrical and heat resistance performance.

[0068] Regarding the curing method, Comparative Example 6 eliminated the stepped curing process, resulting in insufficient release of internal stress in the material. This led to interlayer adhesion failure under subsequent heating conditions, consequently reducing structural stability and service life. In terms of material composition, Comparative Example 7 removed the graphene filler, resulting in the absence of interfacial bonding, increased contact resistance, decreased heat transfer efficiency, and a significant reduction in the battery's high-temperature tolerance.

[0069] Comparative Example 2 lacks a mesh absorbing structure, resulting in insufficient electromagnetic heat control and disrupted electrothermal balance, making it prone to abnormal electrolyte reactions during use. Comparative Example 3 omits a thermal buffer transition layer, failing to buffer the stress caused by thermal deformation, making the layers highly susceptible to separation at high temperatures, ultimately leading to the risk of thermal runaway. Comparative Example 4 replaces the mask preparation material and performs a peeling process, damaging the layer edge structure, reducing overall adhesion strength, and significantly decreasing the current collector's mechanical reliability.

[0070] In summary, the mesh absorbing structure, optimized material ratio, stepped curing process, and thermal buffer layer specified in this invention can synergistically improve the current collector interface strength, heat resistance, and electrochemical performance, effectively avoiding defect problems.

[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent substitutions, and improvements made by those skilled in the art to the above embodiments without departing from the scope of the technical solution of the present invention, based on the technical essence of the present invention, shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. A high-temperature resistant functional current collector, characterized in that, include: The system comprises a polymer substrate layer and a metal layer, with an absorbing layer between the polymer substrate layer and the metal layer. The absorbing layer is a modified metal mesh structure formed on the side of the metal layer facing the polymer substrate layer. The modified metal mesh structure is an integrated composite functional structure composed of a metal mesh and absorbing material filling the mesh gaps.

2. The high-temperature resistant functional current collector according to claim 1, characterized in that, It also includes a thermal buffer transition layer, which is located between the microwave absorbing layer and the polymer substrate layer.

3. The method for preparing the high-temperature resistant functional current collector according to claim 1, characterized in that, Includes the following steps: S1: Metal foil pretreatment; S2: Photosensitive polyimide is coated on one side of a metal foil, and a grid-like mask gap is formed after ultraviolet exposure and development; S3: Apply a microwave absorbing enhancement layer slurry to one side of the metal foil with a grid-like mask gap, so that the slurry fills the mask gap and forms a composite metal foil with a microwave absorbing modified metal grid structure. S4: High-temperature curing of composite metal foil with microwave-absorbing modified metal mesh structure; S5: Hot-press the side of the composite metal foil with the microwave-absorbing modified metal mesh structure to the polymer substrate.

4. The method for preparing the high-temperature resistant functional current collector according to claim 3, characterized in that: The metal foil pretreatment in step S1 is plasma cleaning, and the cleaning gas is a mixture of Ar and H2.

5. The method for preparing the high-temperature resistant functional current collector according to claim 3, characterized in that, In step S2, a 50-100 μm mesh-free area is reserved at the edge of the metal foil.

6. The method for preparing the high-temperature resistant functional current collector according to claim 3, characterized in that: The microwave absorbing reinforcement layer slurry comprises 10-20% by mass of nano-silicon nitride, 3-8% of graphene, and 5-12% of organic binder.

7. The method for preparing the high-temperature resistant functional current collector according to claim 3, characterized in that: Between steps S4 and S5, the following steps are also provided: applying a heat buffer material to one side of the composite metal foil with a wave-absorbing modified metal mesh structure and curing it.

8. The method for preparing the high-temperature resistant functional current collector according to claim 7, characterized in that: The heat buffer material comprises the following components by mass fraction: 40-50% modified silicone resin, 20-30% boron nitride nanosheets, 10-15% silica aerogel, 0.3-0.5% platinum catalyst, and 2-4.5% epoxy silane coupling agent; The curing process is a stepped curing process, including the following stages: Curing at 75-80℃ for 40-45 seconds in air atmosphere to induce gelation; Curing at 120-130℃ for 80-90 seconds under N2 atmosphere to form crosslinks; Curing is carried out under vacuum at 60-65℃ for 4-5 minutes to allow the product to mature.

9. An electrode sheet, characterized in that: The high-temperature resistant functional current collector is prepared by the method described in claim 1 or 2, or any one of claims 3 to 8.

10. A battery, characterized in that: It includes the electrode sheet as described in claim 9.